The modified characteristics finite element method for time-dependent Darcy-Brinkman problem. Issue 1 (7th January 2019) - Liao, Cheng; Huang, Pengzhan
Abstract : Purpose: This study aims to capture the effective behavior of double-diffusion problem, which arises from the combined heat and mass transfer in porous medium and develop the modified characteristics finite element method. Design/methodology/approach: The proposed finite element method deals with the nonlinear term temporal term by modified characteristics method. Then, the authors compute the velocity, pressure, temperature and concentration using the decoupled technique. Finally, to show the efficiency of the method, the authors give some numerical examples. Findings: From the numerical results, one can see that the method has a good accuracy, which shows that the method can simulate this Darcy–Brinkman problem well. Originality/value: The originality lies in the fact that the proposed scheme is the first time for solving the Darcy–Brinkman problem, which is a more complicated model, and includes the velocity, pressure, temperature and concentration.